ASCENDE-RT: An Analysis of Treatment-Related Morbidity for a Randomized Trial Comparing a Low-Dose-Rate Brachytherapy Boost with a Dose-Escalated External Beam Boost for High- and Intermediate-Risk Prostate Cancer - Rodda, Sree; Tyldesley, Scott; Morris, W. James; Keyes, Mira; Halperin, Ross; Pai, Howard; McKenzie, Michael; Duncan, Graeme; Morton, Gerard; Hamm, Jeremy; Murray, Nevin (International journal of radiation oncology, biology, physics, 2017)
To report the genitourinary (GU) and gastrointestinal (GI) morbidity and erectile dysfunction in a randomized trial comparing 2 methods of dose escalation for high- and intermediate-risk prostate cancer. ASCENDE-RT (Androgen Suppression Combined with Elective Nodal and Dose Escalated Radiation Therapy) enrolled 398 men, median age 68 years, who were then randomized to either a standard arm that included 12 months of androgen deprivation therapy and pelvic irradiation to 46 Gy followed by a dose-escalated external beam radiation therapy (DE-EBRT) boost to 78 Gy, or an experimental arm that substituted a low-dose-rate prostate brachytherapy (LDR-PB) boost. At clinic visits, investigators recorded GU and GI morbidity and information on urinary continence, catheter use, and erectile function. Exclusion of 15 who received nonprotocol treatment and correction of 14 crossover events left 195 men who actually received a DE-EBRT boost and 188, an LDR-PB boost. Median follow-up was 6.5 years. The LDR-PB boost increased the risk of needing temporary catheterization and/or requiring incontinence pads. At 5 years the cumulative incidence of grade 3 GU events was 18.4% for LDR-PB, versus 5.2% for DE-EBRT (P<.001). Compared with the cumulative incidence, the 5-year prevalence of grade 3 GU morbidity was substantially lower for both arms (8.6% vs 2.2%, P=.058). The 5-year cumulative incidence of grade 3 GI events was 8.1% for LDR-PB, versus 3.2% for DE-EBRT (P=.124). The 5-year prevalence of grade 3 GI toxicity was lower than the cumulative incidence for both arms (1.0% vs 2.2%, respectively). Among men reporting adequate baseline erections, 45% of LDR-PB patients reported similar erectile function at 5 years, versus 37% after DE-EBRT (P=.30). The incidence of acute and late GU morbidity was higher after LDR-PB boost, and there was a nonsignificant trend for worse GI morbidity. No differences in the frequency of erectile dysfunction were observed.